2001
DOI: 10.1128/jb.183.22.6590-6597.2001
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio fischeriOuter Membrane Protein OmpU Plays a Role in Normal Symbiotic Colonization

Abstract: The nascent light-emitting organ of newly hatched juveniles of the Hawaiian sepiolid squid Euprymna scolopes is specifically colonized by cells of Vibrio fischeri that are obtained from the ambient seawater. The mechanisms that promote this specific, cooperative colonization are likely to require a number of bacterial and host-derived factors and activities, only some of which have been described to date. A characteristic of many host-pathogen associations is the presence of bacterial mechanisms that allow att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
56
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 48 publications
3
56
1
Order By: Relevance
“…One complete ORF was identified and named ompU. The deduced OmpU protein sequence is 330 aa long and is 75 % identical to OmpU from V. cholerae (Sperandino et al, 1996), 59 % identical to OmpU of V. fischeri (Aeckersberg et al, 2001) and 47 % identical to OmpL of Photobacterium profundum (Welch & Bartlett, 1996).…”
Section: Identification and Mutagenesis Of The Ompu Genementioning
confidence: 99%
See 2 more Smart Citations
“…One complete ORF was identified and named ompU. The deduced OmpU protein sequence is 330 aa long and is 75 % identical to OmpU from V. cholerae (Sperandino et al, 1996), 59 % identical to OmpU of V. fischeri (Aeckersberg et al, 2001) and 47 % identical to OmpL of Photobacterium profundum (Welch & Bartlett, 1996).…”
Section: Identification and Mutagenesis Of The Ompu Genementioning
confidence: 99%
“…In addition, a null mutation in the V. fischeri ompU gene also showed an increased sensitivity to membrane-disrupting agents such as bile. However, this observation may indicate the importance of OmpU in maintaining membrane integrity as opposed to survival within the intestinal environment (Aeckersberg et al, 2001).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When a sufficient cell density is reached, the bacteria luminesce, providing the counterillumination ability believed to be an antipredation mechanism for the squid host (see reference 49 for a review). Various studies characterizing the Vibriosquid symbiosis have identified several genetic determinants involved in establishing this association (2,14,48,50,52); however, much remains to be learned about how these symbiotic partners interact.…”
mentioning
confidence: 99%
“…More recently identified colonization factors include RscS, a sensor kinase hypothesized to regulate symbiosis-specific genes (52), and OmpU, an outer membrane protein (2). Because colonization appears to require active participation on the part of both the bacterium and the squid host (36), it is likely that this exclusive association depends upon numerous additional host and bacterial genes.…”
mentioning
confidence: 99%